Freshwater Ostracoda (Crustacea) of Diyarbakir Province, including a new report for Turkey - (:unkn) unknown (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2011)
During the summer (July-August) of 2007, a total of 23 freshwater ostracods belonging to 14 genera were collected from 50 out of 90 different bodies of water in Diyarbakir. Of these 23 finds, Herpetocypris intermedia is a new report for Turkish ostracod fauna. In addition, 11 species (Ilyocypris decipiens, I. inermis, Eucypris virens, Herpetocypris brevicaudata, Psychrodromus fontinalis, Isocypris beauchampi, Potamocypris similis, P unicaudata, P arcuata, Limnocythere stationis, and L. inopinata) are reported from this city for the first time. The geographical distribution of some species is extended into the eastern parts of Turkey. Our results also suggest that species with cosmopolitan characteristics tend to have a wide distribution within a variety of habitats.
Keywords: Ostracoda; new report; Herpetocypris intermedia; distribution; Diyarbakir; Turkey